2015
DOI: 10.1007/s12237-015-9977-8
|View full text |Cite
|
Sign up to set email alerts
|

Community Structure and Abundance of Benthic Infaunal Invertebrates in Maine Fringing Marsh Ecosystems

Abstract: Fringing marshes are abundant ecosystems that dominate the New England coastline. Despite their abundance, very little baseline data is available from them and few studies have documented the ecosystems services that they provide. This information is important for conservation efforts as well as for an increased understanding of how fringing marshes function compared to larger marsh meadow systems. Benthic infaunal invertebrates were sampled from cores collected from Spartina alterniflora-dominated low marsh, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 90 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…While we predicted that compounding abiotic and predation pressure would limit invertebrate community diversity in tidal freshwaters, taxonomic richness generally increased with increasing tidal height. High tidal freshwater wetlands may represent a peak in ecotonal diversity, which is commonly observed in aquatic–terrestrial transition zones (Décamps & Naiman, ; MacKenzie, Dionne, Miller, Haas, & Morgan, ; Tonkin, Stoll, Jähnig, & Haase, ), and at the nexus of other adjoining ecosystem types (Grytnes, Heegaard, & Ihlen, ; Magura, ), as many taxa were found only at these sites. These taxa included many semi‐aquatic or littoral specialists (sensu Merritt et al., ) that may use these sites during the ebb tide and may experience prolonged inundation as a stressor.…”
Section: Discussionmentioning
confidence: 99%
“…While we predicted that compounding abiotic and predation pressure would limit invertebrate community diversity in tidal freshwaters, taxonomic richness generally increased with increasing tidal height. High tidal freshwater wetlands may represent a peak in ecotonal diversity, which is commonly observed in aquatic–terrestrial transition zones (Décamps & Naiman, ; MacKenzie, Dionne, Miller, Haas, & Morgan, ; Tonkin, Stoll, Jähnig, & Haase, ), and at the nexus of other adjoining ecosystem types (Grytnes, Heegaard, & Ihlen, ; Magura, ), as many taxa were found only at these sites. These taxa included many semi‐aquatic or littoral specialists (sensu Merritt et al., ) that may use these sites during the ebb tide and may experience prolonged inundation as a stressor.…”
Section: Discussionmentioning
confidence: 99%
“…Contente et al, 2010;Campos et al, 2015), polychaetes, crustaceans (e.g. Mackenzie et al, 2015) and birds (e.g. Britto & Bugoni, 2015), but there are rare studies on insect groups conducted at these environments (see Giberson et al, 2001;Mackenzie, 2005;Dummel et al, 2011;Bolico et al, 2012;Gantes et al, 2013;Rodrigues et al, 2017).…”
mentioning
confidence: 99%
“…Generally higher abundance and diversity has been reported for low marsh and tide flats due to receiving higher rates of deposited food sources and frequent inundation with supply of larvae (specifically planktonic) from nearby intact marshes (Mackenzie et al 2015, Tanner et al 2002, Kneib 1984. Overall, marine invertebrate community composition has been shown to resemble nearby reference marsh community within 3-4 years (Moy and Levin 1991, Levin et al 1996, Ray 2000, French 2004) though some deviations from this have been reported for marshes in Connecticut, which took several decades (11-21 years) to restore invertebrate community (Warren et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These invertebrates are important components of estuary communities, influencing overall marsh productivity and food web health. Many species of invertebrates, like the tube-dwelling Polychaeta worms stabilize deposited sediments (MacKenzie et al 2015). Species of Amphipoda consume plant materials (Levin et al 2001), promote decomposition (Henriksen et al 1983) and provide dissolved food resources for filter feeders (MacKenzie et al 2015).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
See 1 more Smart Citation